Injection Therapy for Stress Urinary Incontinence: A Review of Bulking Agents - Muzaffarovna, Mukhammadzhonova Mohidil (International Journal of Integrative and Modern Medicine, 2024)
Stress urinary incontinence (SUI) remains a significant medical and social issue, affecting millions of women worldwide. The literature identifies SUI as a prevalent condition, particularly among women aged 30-65, with risk factors including childbirth, pelvic surgery, and menopause. Despite the availability of numerous treatments, periurethral injections using bulking agents have gained attention for their minimally invasive nature. However, limited comprehensive data is comparing their long-term efficacy and safety. This review examines the etiopathogenesis, diagnosis, and treatment options for SUI, focusing on periurethral injections. A systematic review of Russian and international sources was conducted, analyzing the effectiveness of various bulking agents such as autologous fat, silicone, and hyaluronic acid derivatives. Findings indicate that while periurethral injections offer a promising alternative to traditional surgical methods, their success is contingent on the choice of material, with efficacy rates varying from 45% to 90%. Moreover, complications such as urinary retention, infection, and potential migration of the material were noted. The study underscores the need for further research to identify optimal materials that balance long-term efficacy with minimal side effects. The findings have significant implications for improving treatment protocols and patient outcomes in managing SUI.